Penggunaan Merek Atas Peningkatan Pendapatan Dan Perlindungan Hukum Terhadap Merek UMKM Sego Pedes Basman - Elvira Rosa Astrianto; Kiara Dhafa Nahdah Azalia; Natalia Evira Palit; Ramot Andrew Christian Siagian; Rumagam Amputua Hasian Siregar; Asep Saripudin (International Forum of Researchers and Lecturers, 2024)
Micro, Small and Medium Enterprises or what are usually called MSMEs have an important role in national economic development efforts in Indonesia. From year to year, the number of MSMEs in Indonesia has increased quite rapidly. However, there are still many MSME business actors who have not registered their trademarks due to limited capital and information about the benefits they receive. Trademark registration is considered to increase people's purchasing power towards a product because it can be used as a characteristic or differentiator from other products. Trademark registration can also receive legal protection for a product's trademark. Therefore, the use and legal protection of a trademark is considered very important for MSMEs. This research discusses the use of brands to increase income and legal protection for the Sego Pedes Basman Umkm Brand. The research uses qualitative research with a normative juridical approach method.